Chór żeński z Sofii im. Morfowa Prokopowa Bułgaria. (Gdańsk : [s.n.], 1967)
Afisz inf. o koncercie 22.06.1967 r.
Keywords: Życie muzyczne -- Polska -- Gdańsk -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne